2022
DOI: 10.1016/j.heliyon.2021.e08676
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to pay for the ecological restoration of an inland freshwater shallow lake: case of Lake Malombe, Malawi

Abstract: Lake Malombe is ranked among the most vulnerable inland freshwater shallow lakes in Malawi. The lake has lost over US$79.83 million ecosystem service values from 1999 to 2019 due to rapid population growth, increased poverty, landscape transformation, and over exploitation-hampering the effort to achieve United Nations (UN) Sustainable Development Goals (SDGs), in particular, life underwater (SDG 14), life on land (SDG 15), climate action (SDG 13), and no poverty (SDG 1) and Aichi Biodiversity Targets. In line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 94 publications
0
2
0
Order By: Relevance
“…The Lancaster Demand Theory [ 28 ] counters by confirming that consumers are assumed to derive utility not as directly from consuming goods or services but rather from some characteristics of the goods or services being consumed [ 29 ]. Solution approaches for valuation include direct and indirect methods such as the contingent valuation method, travel cost method, conjoint analysis, hedonic pricing method, choice experiments, advertising behaviour, choice ranking, and contingent rating [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Lancaster Demand Theory [ 28 ] counters by confirming that consumers are assumed to derive utility not as directly from consuming goods or services but rather from some characteristics of the goods or services being consumed [ 29 ]. Solution approaches for valuation include direct and indirect methods such as the contingent valuation method, travel cost method, conjoint analysis, hedonic pricing method, choice experiments, advertising behaviour, choice ranking, and contingent rating [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Different authors used CVM to elicit the contribution of local people to the improvement of freshwater ecosystem services. For instance, Makwinja et al (2022) estimated the public's WTP for ecosystem restoration of a shallow lake in Malawi. They reported that more than half of the respondents were willing to pay an average amount of US$28.4 per year to restore Lake Malombe.…”
Section: Introductionmentioning
confidence: 99%